(untitled) (Revista de Estudos da Linguagem, 2024)
In the Republic of Equatorial Guinea (REG), Spanish, French, and Portuguese are official languages. Additionally, the population also uses African languages (Fang, Pichi, Bube, Fa d’Ambô, among others). With rural-urban migration increasing, languages of different ethnic groups have been restricted to their traditional territories. Alongside Spanish, in recent years, Fang and Pichi have become the most spoken languages, especially in urban settings by an ever-growing young population. Here, our goal is to describe and analyze the linguistic situation in the country, the maintenance or obsolescence of REG’s languages, and the role of the official languages (Spanish, French, and Portuguese).